Peptide nucleic acid restores colistin susceptibility through modulation of MCR-1 expression in Escherichia coli. (17th May 2020) - Wang, Xiaoming; Wang, Yao; Ling, Zhuoren; Zhang, Chaoyang; Fu, Mingming; Wang, Yang; Wang, Shaolin; Zhang, Suxia; Shen, Zhangqi
Abstract: Background: Plasmid-mediated mechanisms of drug resistance accelerate the spread of polymyxin resistance, leaving clinicians with few or no antibacterial options for the treatment of infections caused by MDR bacteria, especially carbapenemase-producing strains. Objectives: To evaluate the associations among promoter sequence variation, mcr-1 expression, host factors and levels of colistin resistance and to propose antisense agents such as peptide nucleic acids (PNAs) targeting mcr-1 as a tool to restore colistin susceptibility through modulation of MCR-1 expression in Escherichia coli . Methods: A β-galactosidase assay was performed to study mcr-1 promoter activity. Quantitative real-time PCR and western blot assays were used to identify the expression level of MCR-1 in WT strains and transformants. Three PNAs targeting different regions of mcr-1 were designed and synthesized to determine whether they can effectively inhibit MCR-1 expression. MIC was measured to test colistin susceptibility in the presence or absence of PNA-1 in mcr-1 -carrying E. coli . Results: Variation in the mcr-1 promoter sequence and host species affect promoter activity, MCR-1 expression levels and colistin MICs. One PNA targeting the ribosome-binding site fully inhibited the expression of mcr-1 at a concentration of 4 μM, resulting in significantly increased susceptibility to colistin. The MIC90 of colistin decreased from 8 to 2 mg/L ( P < 0.05) in the presence of 4 μM PNA. Conclusions: These findings suggest that the antisense approach is a possible strategy to combat mcr-1 -mediated resistance as well as other causes of emerging global resistance.